Perubahan Kurikulum Pendidikan Agama Islam - Endang Kaswati; Farizal Farizal; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article aims to investigate the changes that have occurred in the development of the Islamic religious education curriculum. Islamic religious education has an important role in shaping the character of students and developing their understanding of Islamic teachings. This research uses a descriptive-analytical method by analyzing related documents, school policies, and interviews with related parties. It is hoped that the results of this research will provide a clear picture of how changes in the development of the Islamic religious education curriculum contribute to improving the quality of education. Based on the results of research in the field, it was found that learning activities make it very easy for us to get further information about innovative curriculum developments using internet-based learning media and determining the applications that are of interest to students nowadays, including the applications used by teachers, the IG application. , interactive Power Point, Tiktok, Quiziz, Classroom and other supporting applications. Based on the researcher's explanation, it was found that in innovation in Islamic religious education, curriculum development in the era of revolution 4.0 can also be applied to visuals for learning, flipped classrooms, centered on students learning the learning process, results-based learning, collaborative spaces.